Understanding the Concept of al-Ijarah in Sharia Economics - Felisha Edelisia Herawan (Rihlah Iqtishad: Jurnal Bisnis dan Keuangan Islam, 2024)
This research aims to understand the concept of al-Ijarah from a Sharia economic perspective based on the Hadith of the Prophet and the quality of hadith that discuss al-Ijarah by first executing the hadith Naqd al-Sanad, Naqd al-Matan, and I-Tibal about martyrdom and Muttabian, as well as providing detailed syār (explanation). A complete review of representative hadiths with the aim of providing a legal basis in the context of al-Ijarah activities. This study explores a large number of hadiths and summarizes them into topics of discussion using the Taqriji al-Hadith bi-al-Faz and Taqriji al-Hadith bi-al-Mawdui methods. Next, one of the hadiths which represents various hadiths related to al-Ijarah will be discussed comprehensively and in detail. Ijarah is a concept in Islam that refers to renting or renting. In carrying out the ijarah there are conditions and harmony. Ijarah is also divided into two forms, namely, ijarah for benefits and ijarah for work. In Islam, the practice of ijarah (renting) is supported by various arguments from Islamic legal sources. Some of these arguments, among others, come from the Al-Qur'an, hadith, and the consensus of ulama (ijma').